Preparedness of pre-intern medical graduates of three universities in Sri Lanka to diagnose and manage anaphylaxis - Chandrani Nirmala Wijekoon; Indika Wettasinghe; Dinithi Fernando; Arosha Sampath Dissanayake; Malinda Gunawardana; Gayani Minuwanpitiya; Palinda Thenuwara (BMC Medical Education, 2021)
Abstract Background Early recognition and the optimal management of anaphylaxis saves lives but studies from different countries have demonstrated gaps in knowledge and practices between healthcare workers. There is a paucity of such data from Sri Lanka. We assessed knowledge, perception and self-confidence in the diagnosis and management of anaphylaxis amongst pre-intern medical graduates who would soon become first-contact doctors attending emergencies. Methods This cross-sectional study included pre-interns who graduated with Bachelor of Medicine, Bachelor of Surgery (MBBS) degrees in 2019 from three Sri Lankan universities with differing undergraduate curricula. Using consecutive sampling data were collected within four months of the final-MBBS examinations with a self-administered questionnaire and the answers on case diagnosis and management were used as the basis of outcome scores. Results 385 participants responded (response rate: 91.5%). 16.4% correctly identified all anaphylaxis triggers. Only 7.3% correctly diagnosed all ten case scenarios and 34.5% all seven cases of anaphylaxis. 98.2 and 97.9% correctly identified 1:1000 adrenaline as the first-line treatment and the intramuscular route. 9.9% would preferentially but incorrectly use the intravenous route if access was available. Only 79.2 and 55.6% knew the correct adult and paediatric doses of adrenaline and 50% agreed that follow-up care was needed. The mean scores for case diagnosis and management of anaphylaxis were 7.7/10 ± 1.4 and 16.9/20 ± 1.9, respectively. Multiple linear regression indicated that the final MBBS results classification (class of degree or no class indicated) was a positive predictor of case diagnosis score [class vs no class: B = 0.662 (95% CI 0.347–0.978), p < 0.001] and being a graduate of University 2 [B = 1.568 (95% CI 1.182–1.953), p < 0.001] and passing with a class at final MBBS [B = 0.716 (95% CI 0.319–1.113), p < 0.001] were positive predictors of management score. Self confidence in diagnosing and managing anaphylaxis were rated as 79.7 and 62.1% and there was a positive correlation between knowledge and perception scores and self-confidence (case-diagnosis: r pb = 0.111, p = 0.03; management: r pb = 0.164, p = 0.001). Conclusions Knowledge, perception and self confidence in the diagnosis and management of anaphylaxis was sub optimal amongst pre-interns and we identified areas that need improvement. A higher MBBS qualification classification was a predictor for correct diagnosis and management and confidence in diagnosis and management positively correlated with knowledge and perception scores. Further and enhanced educational and training strategies are needed for this life threatening emergency condition.